From Crisis to Competitiveness: A Schumpeterian Perspective on Entrepreneurial Orientation and SME Sustainability in Malaysia - Lim, Siok Kian Cathy; Yeo, Chu May Amy; Yip, Mum Wai; Tay, Lee Chin (INTI International University, 2025)
Small and medium-sized enterprises (SMEs) form the backbone of Malaysia’s economy but continue to face high failure rates due to market volatility, resource limitations, and technological disruptions. The COVID-19 crisis further intensified these challenges, exposing structural weaknesses that threaten both performance and survival. While Entrepreneurial Orientation (EO) has long been recognised as a key driver of business success, the effectiveness of its dimensions: innovativeness, proactiveness, and risk-taking, in ensuring post-crisis sustainability remains underexplored from a Schumpeterian perspective. This study investigates the relationship between EO dimensions and firm performance among Malaysian SMEs, focusing on how entrepreneurial behaviour contributes to competitiveness in the aftermath of crisis. Using data analysed through IBM SPSS and AMOS, the results reveal that only risk-taking shows a significant negative effect on firm performance, whereas innovativeness and proactiveness are not significant predictors. These findings suggest that excessive or unmanaged risk may weaken firm resilience in volatile environments, while innovation and proactive strategies may require longer time horizons to yield benefits. By framing the analysis within Schumpeter’s theory of innovation and creative destruction, this study provides empirical insights into how SMEs can transition from crisis to competitiveness. It highlights the importance of balanced entrepreneurial behaviour, where calculated risk-taking, continuous learning, and adaptive strategies are essential for long-term sustainability in uncertain economic conditions.